Neptune rising [undersea observatory]. - Fairly, P.
A research team from a consortium of Canadian and US universities and research laboratories has initiated a program called NEPTUNE (North-East Pacific Time-Series Underse Networked Experiments), which aims to literally wire about 200,000 square kilometers of ocean floor off the coasts of Oregon, Washington and British Columbia, using hundreds of sensors, cameras and instruments powered from shore via an undersea 100-kilowatt grid. Linked together, the instruments are part of a multi-gigabit per second data network designed to continuously provide information onto the Internet, where scientists on land can access it. With NEPTUNE, oceanographers are aiming for an observatory infrastructure that is robust enough to last 30 years and versatile enough to provide power to, and stream data from, essentially any kind of instrument an ocean scientist might need.
Keywords: Canadian universities; Internet; Neptune; North-East Pacific Time-Series Underse Networked Experiments; US universities; Cameras; Observatory infrastructure; Oceanographers; Sensors; Undersea observatory